The Subsystem of Numerals in Catalan Sign Language: Description and Examples from a Psycholinguistic Study. - Fuentes, Mariana; Tolschinsky, Liliana (Sign Language Studies)
Linguistic descriptions of sign languages are essential to support their linguistic status and to preserve the cultural background of the Deaf communities that use and recreate them. We describe the subsystem of cardinal numbers in Catalan Sign Language (LSC) in the variety used in Barcelona. The description includes the parameters of hand-shape, orientation, location, direction, and movement. We also illustrate, with some results from a psycholinguistic study, how LSC's number features influence the transcoding behavior of deaf children learning the language. Most of the errors the students commit can be explained by overgeneralization of LSC's number-system features.